Pinay magnificat living out our theology (National Council of Churches in the Philippines, 2017)
"This anthology of ecumenical women's articulations is a humble offering as we celebrate and continue to recognize that we who believe in women's emancipation must collectively release ourselves from ideologies and theologies that shackle us. This collection of narratives is the fruit of ecumenical women's participation in the struggle of Filipino women to be free from national, class and gender oppression ..." -- Foreword, page 1.